Lignocellulosic Biomass-derived biogas: a review on sustainable energy in Malaysia - Ab. Aziz, Izzah Farhana; Demirci, Ali; Hamzah, Muhammad Hazwan; Omar, Rozita; Jamali, Nur Syakina; Katibi, Kamil Kayode; Mohammed, Abdulsalam (Malaysian Palm Oil Board, 2024)
Lignocellulosic Biomass (LCB) is regarded as a potentially sustainable alternative resource to fossil fuels. To address concerns related to environmental degradation and geopolitical tensions arising from resource scarcity, the global focus shifted towards developing and utilising sustainable and Renewable Energy (RE) technologies. Biogas technology has attracted attention due to its promising potential to generate energy from agro-waste and the preservation of natural resources. Therefore, this review explores the potential of utilising RE, specifically focusing on its practical implementation in Malaysia. It critically evaluates pre-treatment methods suitable for the country’s prevalent biomass sources, offering insights into their applicability. Additionally, the article provides updated data on Malaysia’s strategy to advance RE production, particularly in biogas. Despite considerable efforts, there is a notable gap in comprehensively assessing the impact of pretreatment methods on LCB in Malaysia’s biogas production. Hence, this article critically assesses recent advancements to address this gap, focusing on potential challenges and the comparative effectiveness of treatment techniques in Malaysian biogas production. It is with the aim to shed light on associated drawbacks and suggest means to enhance performance. Finally, this article ends by reviewing economic analyses for pre-treatment in LCB, focusing on efficient biogas production.